SKRINING HIPERKOLESTEROL PADA MASYARAKAT DI WILAYAH KERJA PUSKESMAS II DENPASAR UTARA - Putu Intan Daryaswanti (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2019)
Hyper cholesterol is a risk factor for cardiovascular disease which is a major cause of death and illness worldwide. Chronic and non-infectious diseases are generally caused by bad lifestyle factors, which can actually be modified. Some of the factors that are at risk for heart disease and stroke are hypertension, cigarette consumption, diabetes, lack of physical activity, unhealthy diets, dyslipidemia, overweight and obesity. The purpose of this community service was to find out an overview of the prevalence of hypercholesterolemia in the area, this screening activity was also expected to be able to initiate cadres and the community to be more active in implementing post-natal activities. Method: This community service activity uses the Community Service approach, by carrying out screening activities forhypercholesterolemia through cholesterol checks on the people in Banjar Tulang Ampian and Banjar Kerta Sari Pemecutan Kaja Village, North Denpasar. Results: A total of 31 people netted had high cholesterol levels of 40240 mg / dL which was dominated by women (63.49%), the most age group was ?51 years (38.62%), most subjects were self-employed / traders (38 , 10%). Conclusion: Increased blood cholesterol levels with age increase are associated with a reduction in cholesterol elimination as bile salts and a decrease in receptors that mediate the clearance process of plasma LDL. Cholesterol levels increase with increasing age and the incidence of coronary heart disease.